Papers on the 1962 election : fifteen papers on the Canadian general election of 1962 - Meisel, John (Heritage., 1964)
The essays included in this volume do not follow any one theme, nor are they given unity by a shared frame of reference. Each author dealt with some aspect of the 1962 election without any concern with what was being attempted by the others.